A Combined Robotic and Cognitive Training for Locomotor Rehabilitation: Evidences of Cerebral Functional Reorganization in Two Chronic Traumatic Brain Injured Patients - Sacco, Katiuscia; Cauda, Franco; D'Agata, Federico; Duca, Sergio; Zettin, Marina; Virgilio, Roberta; Nascimbeni, Alberto; Belforte, Guido; Eula, Gabriella; Gastaldi, Laura; Appendino, Silvia; Geminiani, Giuliano C. (Frontiers in Human Neuroscience, 2011)
It has been demonstrated that automated locomotor training can improve walking capabilities in spinal cord-injured subjects but its effectiveness on brain damaged patients has not been well established. A possible explanation of the discordant results on the efficacy of robotic training in patients with cerebral lesions could be that these patients, besides stimulation of physiological motor patterns through passive leg movements, also need to train the cognitive aspects of motor control. Indeed, another way to stimulate cerebral motor areas in paretic patients is to use the cognitive function of motor imagery. A promising possibility is thus to combine sensorimotor training with the use of motor imagery. The aim of this paper is to assess changes in brain activations after a combined sensorimotor and cognitive training for gait rehabilitation. The protocol consisted of the integrated use of a robotic gait orthosis prototype with locomotor imagery tasks. Assessment was conducted on two patients with chronic traumatic brain injury and major gait impairments, using functional magnetic resonance imaging. Physiatric functional scales were used to assess clinical outcomes. Results showed greater activation post-training in the sensorimotor and supplementary motor cortices, as well as enhanced functional connectivity within the motor network. Improvements in balance and, to a lesser extent, in gait outcomes were also found.